2016
DOI: 10.1016/j.jsxm.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Increase Sexual Dysfunction in Patients with Non-Cancer Pain

Abstract: Introduction Long-term opioid therapy has been found to have a strong impact on the hypothalamic-pituitary-gonadal axis that can be manifested clinically by sexual dysfunction (SD). This event is rarely reported and thus unnoticed and undertreated. Aim To analyze the presence of SD in a large group of patients receiving long-term opioids. Methods A descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…37,38 Although the underlying reasons are not clear because women are only included in 38% of human research studies, hormonal factors, differences in pharmacokinetics and pharmacodynamics may play a significant role. 39 This discrepancy might be explained too much emphasis placed on sexual dysfunction because of a parallel open study of long-term opioid patients in our unit at that time, 40,41 as 67% of males suspected ADRs in our study are loss of libido or erectile dysfunction.…”
Section: Discussionmentioning
confidence: 77%
“…37,38 Although the underlying reasons are not clear because women are only included in 38% of human research studies, hormonal factors, differences in pharmacokinetics and pharmacodynamics may play a significant role. 39 This discrepancy might be explained too much emphasis placed on sexual dysfunction because of a parallel open study of long-term opioid patients in our unit at that time, 40,41 as 67% of males suspected ADRs in our study are loss of libido or erectile dysfunction.…”
Section: Discussionmentioning
confidence: 77%
“…Pain is another common complaint of methadone-maintained patients, which refers to “an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage.” 13 – 16 Due to concerns about opioid dependence as a barrier to pain management, pain is also often undertreated or untreated in addiction treatment practice. 13 , 17 Previous studies have reported a high prevalence of sexual dysfunction in patients with painful conditions (ie, chronic pelvic pain syndrome and chronic low back pain), 18 20 which is particularly high among those with intensive and severe pain. 20 Therefore, we speculate that pain is associated with sexual dysfunction in methadone-maintained patients.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 17 Previous studies have reported a high prevalence of sexual dysfunction in patients with painful conditions (ie, chronic pelvic pain syndrome and chronic low back pain), 18 20 which is particularly high among those with intensive and severe pain. 20 Therefore, we speculate that pain is associated with sexual dysfunction in methadone-maintained patients. However, results of our literature search within major Chinese and English databases (from their inception date to July 24, 2018) showed that no studies have examined the potential effect of pain on sexual function in methadone-maintained patients.…”
Section: Introductionmentioning
confidence: 99%
“…Buprenorphine and tramadol elucidated less hazard on the gonadal hormonal functionality which is attributed to their partial agonistic effect of mu receptors. 48,64,67,68 Furthermore, using opioids through the intrathecal route is found to be associated with higher prevalence of OHG compared to the oral Erectile dysfunction √ -- [121][122][123][124] counterpart. 69 However, opioid-induced hypogonadism is reversible on discontinuation of opioid, even among long-term therapy.…”
Section: The Effect Of Opioids On the Secretion Of Sex Hormonesmentioning
confidence: 99%